Steroid but not Biological Therapy Elevates the risk of Venous Thromboembolic Events in Inflammatory Bowel Disease: A Meta-Analysis. (6th December 2017) - Sarlos, Patricia; Szemes, Kata; Hegyi, Peter; Garami, Andras; Szabo, Imre; Illes, Anita; Solymar, Margit; Petervari, Erika; Vincze, Aron; Par, Gabriella; Bajor, Judit; Czimmer, Jozsef; et al.
Abstract: Background and Aims: Inflammatory bowel disease [IBD] is associated with a 1.5- to 3-fold increased risk of venous thromboembolism [VTE] events. The aim of this study was to determine the risk of VTE in IBD as a complication of systemic corticosteroids and anti-tumour necrosis factor alpha [TNFα] therapies. Methods: A systematic review and meta-analysis was conducted, which conforms to the Preferred Reporting Items for Systematic Reviews and Meta-analyses [PRISMA] statement. PubMed, EMBASE, Cochrane Library and Web of Science were searched for English-language studies published from inception inclusive of 15 April 2017. The population-intervention-comparison-outcome [PICO] format and statistically the random-effects and fixed-effect models were used to compare VTE risk during steroid and anti-TNFα treatment. Quality of the included studies was assessed using the Newcastle–Ottawa scale. The PROSPERO registration number is 42017070084. Results: We identified 817 records, of which eight observational studies, involving 58518 IBD patients, were eligible for quantitative synthesis. In total, 3260 thromboembolic events occurred. Systemic corticosteroids were associated with a significantly higher rate of VTE complication in IBD patients as compared to IBD patients without steroid medication (odds ratio [OR]: 2.202; 95% confidence interval [CI]: 1.698–2.856, p < 0.001). In contrast, treatment with anti-TNFα agents resulted in a 5-fold decreased risk of VTE compared to steroid medication [OR: 0.267; 95% CI: 0.106–0.674, p = 0.005]. Conclusion: VTE risk should be carefully assessed and considered when deciding between anti-TNFα and steroids in the management of severe flare-ups. Thromboprophylaxis guidelines should be followed, no matter the therapy choice.